Association of occupational noise exposure with hypertension: A cross‐sectional study. Issue 2 (30th December 2022) - Wang, Jin; Zhang, Panpan; Wang, Yaning; Wang, Hui; Gao, Yuan; Zhang, Yurong
Abstract: The effects of chronic occupational noise exposure on hypertension are debated. We aimed to investigate the association between occupational noise exposure and the prevalence of hypertension. The cross‐sectional data were collected from 2017 to 2018 using occupational physical examination data from a local aircraft manufacturing enterprise in Xi'an. We categorized occupational noise exposure as high (≥85 dBA) and low noise exposure (< 85 dBA). Logistic regression analysis was performed to evaluate the association between occupational noise exposure and hypertension, and associations were further evaluated using subgroup analyses for age, sex, and body mass index (BMI). Of the 4746 participants (median age, 43 years; 73.4% men), 9.57% (454/4746) had hypertension and 32.4% (1540/4746) were exposed to high noise. Compared to the participants with low occupational exposure to noise, the adjusted odds ratio (OR) for hypertension prevalence was 1.30 (1.05–1.62) for those with high occupational noise exposure. Subgroup analyses revealed that the noise‐hypertension association only existed in young participants (OR, 1.70; 95% CI, 1.21–2.40). This study revealed a harmful association between high occupational noise exposure and hypertension in young adults. The study suggests occupational noise exposure as a target for worksite interventions to prevent hypertension.